Implementation of Salam and Istishna’ Contracts in Islamic Financial Institutions - Badruddin Ibad (Denisya Smart Consulting, 2023)
Islamic financial institutions are continually innovating in the field of financing, one of which is through salam and istishna' contracts. The implementation of these contracts holds significant potential to benefit society, particularly in agriculture and housing sectors. However, obstacles persist in the regulations and policies supporting the implementation of these contracts, alongside a lack of understanding and awareness among the public regarding the concepts and advantages of salam and istishna' contracts. This research utilizes a literature study method by gathering data from academic sources and journals that delve into the concepts of buying and selling within Islamic finance, specifically salam and istishna' contracts. The research aims not only to identify the potential of salam and istishna' contracts in facilitating the agricultural and housing sectors but also to analyze the barriers hindering the implementation of these contracts. The findings demonstrate that salam and istishna' contracts hold significant potential in facilitating financing and investment in agricultural and housing sectors. The implementation of salam contracts can provide easier and more affordable access to financing for farmers, while istishna' contracts can serve as housing financing instruments in line with Sharia principles. However, hurdles remain in the implementation of salam and istishna' contracts, such as a lack of public understanding and supportive regulations. Therefore, efforts are necessary to enhance public understanding of the concepts and benefits of salam and istishna' contracts, along with clear regulations to support the implementation of these contracts within Islamic financial institutions